Hormonal fine-tuning of clock in decidual region of mouse placenta by dopamine, melatonin, insulin, leptin and ghrelin - Lužná, Vendula; Liška, Karolína; Sládek, Martin; Sumová, Alena (Placenta, 2021)
INTRODUCTION: The maternal part of the rodent placenta harbors a circadian clock which robustly responds to glucocorticoids, however, its sensitivity to other hormones has not been elucidated. In this study, we tested five selected hormones (dopamine, melatonin, insulin, leptin and ghrelin) for their effectiveness to affect the clock in decidual region of mouse placenta in vitro. METHODS: We administered the hormones or corresponding vehicles at various time points over 24 h to organotypic placental explants of mPer2Luc mice containing the decidua basalis (DB) region and monitored their effects on amplitude, period, median expression level (mesor) and phase of PER2-driven bioluminescence rhythms. RESULTS: Dopamine significantly increased the amplitude, robustly dampened the mesor, and during a narrow time interval (corresponding to daytime) induced phase delays of the rhythms. In contrast, melatonin had no effect on amplitude, but induced phase advances of the rhythms at the opposite time window than dopamine (corresponding to nighttime). Leptin and ghrelin, but not insulin, slightly increased amplitudes and moderately modulated phase delays of the clock, suggesting that the DB clock, in contrast to other peripheral clocks, is rather resilient to abrupt changes in levels of feeding- and metabolism-related hormones. DISCUSSION: The results demonstrate for the first time that dopamine and melatonin exhibit delicate yet specific effects on parameters of the DB clock and may thus potentially contribute to fine-tuning of its phase under in vivo conditions. It also implies that dysregulation of their levels, which accompany various pathologies, may account for malfunction of the clock in DB.
Keywords: Circadian Clocks; hormony; Male; Pregnancy; těhotenství; Placenta; mužské pohlaví; dopamin; cirkadiánní rytmus; Melatonin; Circadian Rhythm; Phase response curve; Dopamine; Hormones; Decidua basalis; placenta; Animals; ženské pohlaví; zvířata; myši; Circadian clock; Mice; Female; PER2; cirkadiánní hodiny